Krepitev medijske svobode: Varstvo novinarjev v Evropi, sovražni govor, dezinformacije in vloga platform (University of Maribor Press, 2022)
Strengthening Media Freedom: Protecting Journalists in Europe, Hate Speech, Fake News and the Role of Platforms. The book contributes to the construction of a unified framework for media freedom in the European Union. In this regard, it outlines the position of media freedom upon the accession of countries to the EU and the emerging legal framework for the protection of media freedom as the foundation of democracy in the EU Member States. From the initial approach to the media as one of the service sectors that should be provided with the benefits of the single market, today the special nature of the media as an actor in ensuring democracy is in the foreground. The book discusses the competences of the EU to adopt legal standards of media freedom and recent legislative proposals in this area. Also highlighted are the area of preventing the spread of fake news, SLAPP lawsuits aimed at intimidating and professionally discrediting their targets, and the area of media ownership and funding. Special chapters are dedicated to online hate speech and whistleblower protection in the EU. The authors note that a greater challenge than the adoption of legislation to protect media freedom in the EU will be its implementation in practice.